Polypropylene composite material as well as preparation method and application thereof

By formulating a polypropylene composite material containing flame retardant, antioxidant, light stabilizer and composite pigment, the problem of lack of light-colored polypropylene composite materials suitable for ultraviolet laser marking in the prior art is solved, and the effect of clear marking after ultraviolet laser marking is achieved, and it is suitable for fine processing and manufacturing needs in various industries.

CN119842147APending Publication Date: 2025-04-18KINGFA SCI & TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411967267.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The lack of light-colored polypropylene composite materials suitable for ultraviolet laser marking in the prior art, resulting in the inability to meet higher processing and manufacturing needs under the demand for fine marking.

Method used

By preparing a polypropylene composite material, its components include 95-105 parts of polypropylene resin, 5-20 parts of flame retardant, 1-5 parts of antioxidant, 1-3 parts of light stabilizer and 0.5-5 parts of composite pigment. The composite pigment is compounded from titanium dioxide and carbon black. The weight ratio of titanium dioxide to carbon black is 2500-20,000:1, and is used to prepare a light-color flame-retardant polypropylene composite material that can be used for ultraviolet laser marking.

Benefits of technology

This polypropylene composite material can present a clear laser marking effect after ultraviolet laser marking. It is widely used in industries such as electronic components, white appliance shells, automotive interior and exterior decorations, meeting the needs of more refined processing and manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and particularly relates to a polypropylene composite material as well as a preparation method and application thereof. Specifically, the polypropylene composite material comprises the following components in parts by weight: 95-105 parts of polypropylene resin; 5-20 parts of a flame retardant; 1-5 parts of an antioxidant; 1-3 parts of a light stabilizer; 0.5-5 parts of a composite pigment; the composite pigment is obtained by compounding titanium dioxide and carbon black; the compounding weight ratio of the titanium dioxide to the carbon black is (2500-20000): 1. The polypropylene composite material provided by the invention can be used for ultraviolet laser marking and has a clear laser marking effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a polypropylene composite material and a preparation method and application thereof. Background Art

[0002] As a thermoplastic synthetic resin, polypropylene (PP) has the advantages of low density, electrical insulation, resistance to chemical reagents, excellent weather resistance, easy processing and recycling. It is widely used in industries such as automobiles, home appliances, power tools and packaging.

[0003] In the actual production and manufacturing of parts, manufacturers need to mark the company name, product specifications, serial numbers, anti-counterfeiting information, etc. on the products to improve product identification and achieve production traceability. Traditional polypropylene product identification technologies include chemical silk screen, paint, film, etc., while laser marking uses the high energy density of the laser beam to cause chemical or physical changes in the surface material of the workpiece, thereby leaving a permanent mark on the surface of the workpiece. It has the advantages of no pollution, high speed, high quality, great flexibility, and no contact with the workpiece. Laser marking is gradually replacing traditional identification technology, and its application is becoming more and more extensive, and it has become the mainstream technology in the industry. Infrared laser marking is affected by its natural characteristics such as wavelength, pulse width and current power, and the processing thermal effect is serious, which can no longer meet the needs of more sophisticated processing and manufacturing. Ultraviolet laser marking technology has developed rapidly due to its high single photon energy, which can directly interrupt the intermolecular force, cause non-thermal damage to the material, and then leave a permanent mark on the surface of the material. It has become a reliable choice for material identification technology.

[0004] There are relatively more studies on laser marking, among which infrared laser marking technology is more studied, while ultraviolet laser marking technology is less studied. This is because infrared laser marking technology was developed the earliest, is the most mature in the manufacturing industry, and has a certain inertia of technical routes. Ultraviolet laser marking technology only emerged after the development of demand for fine marking. At present, it is relatively rarely used in the modified plastics industry, and it belongs to a relatively new technical field in terms of industry application. The research objects of modified plastics are mainly engineering plastics such as nylon, polycarbonate and PBT, and there is less research on polypropylene modified materials.

[0005] The existing technology mainly studies engineering plastics such as nylon, polycarbonate and PBT, which is of little reference significance for polypropylene UV laser marking. Therefore, it is of practical significance to provide a light-colored polypropylene composite material that can be used for UV laser marking. Summary of the invention

[0006] The object of the present invention is to provide a light-colored flame-retardant polypropylene composite material which can be used for ultraviolet laser marking.

[0007] Another object of the present invention is to provide a process for preparing the polypropylene composite material.

[0008] Another object of the present invention is to provide an application of the polypropylene composite material.

[0009] The present invention is achieved through the following technical solutions: A polypropylene composite material, characterized in that it comprises the following components in parts by weight: Polypropylene resin 95-105 parts; Flame retardant 5-20 parts; 1-5 parts of antioxidant; 1-3 parts of light stabilizer; Composite pigment 0.5-5 parts; The composite pigment is obtained by compounding titanium dioxide and carbon black; the weight ratio of the titanium dioxide and carbon black is (2500-20000):1.

[0010] Carbon black in composite toner acts as a light absorber to absorb photons.

[0011] In the present invention, the titanium dioxide is a rutile pigment titanium dioxide, preferably with a particle size of 0.20-0.25 μm; the carbon black is selected from the pigment carbon black obtained by acetylene thermal decomposition method, and the particle size of the carbon black is preferably 20-35 nm.

[0012] Preferably, the melt index of the polypropylene resin is 1-30 g / 10 min, the testing conditions are a temperature of 230° C. and a load of 2.16 kg, and the testing standard is ISO 1133-1-2011.

[0013] Preferably, the composite pigment accounts for 1-4 parts by weight in the polypropylene composite material.

[0014] Preferably, the polypropylene resin is selected from at least one of homopolymer polypropylene resin and copolymer polypropylene resin.

[0015] More preferably, the polypropylene resin is selected from homopolypropylene.

[0016] The polypropylene composite material provided by the present invention can be used for ultraviolet laser marking. The wavelength of the light source of the ultraviolet laser marking equipment is usually 355nm. At this wavelength, homopolymer polypropylene has a better marking effect.

[0017] Preferably, the flame retardant is selected from flame retardants containing metal elements, which can enhance the material's absorption of ultraviolet photons and energy conduction, making the marking effect more intense; the metal element is antimony or titanium.

[0018] More preferably, the flame retardant is a flame retardant containing antimony or titanium.

[0019] The reason why flame retardants containing the above metal elements have better effects is speculated to be because the outer electron ionization energy of antimony and titanium metal oxides or complexes is close to the energy of ultraviolet photons, so they can absorb ultraviolet photon energy and undergo transitions, and convert light energy into internal energy, greatly promoting the marking effect.

[0020] Preferably, the antioxidant is selected from phosphite antioxidants and hindered phenol antioxidants; the weight ratio of the phosphite antioxidants to the hindered phenol antioxidants is (1-3):1.

[0021] More preferably, the weight ratio of the phosphite antioxidant to the hindered phenol antioxidant is (1.5-2.5):1.

[0022] Specifically, the phosphite antioxidant is selected from tris(2,4-di-tert-butylphenyl)phosphite; and the hindered phenol antioxidant is selected from pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.

[0023] Preferably, the light stabilizer is selected from at least one of a hindered amine light stabilizer, a benzotriazole light stabilizer, a benzophenone light stabilizer or a hindered benzoate light stabilizer.

[0024] Specifically, the hindered amine light stabilizer is selected from 2,2,6,6-tetramethyl-4-piperidinyl stearate.

[0025] Preferably, the titanium dioxide is selected from rutile titanium dioxide.

[0026] Preferably, the weight ratio of the titanium dioxide to carbon black is (4000-6000):1.

[0027] More preferably, the weight ratio of the titanium dioxide to carbon black is 5000:1.

[0028] The present invention provides a method for preparing the above-mentioned polypropylene composite material, comprising the following steps: (1) Weigh each component according to the ratio, put it into the premixer in turn, and mix for 6-8 minutes to achieve a uniform mixing state; (2) The mixed material is fed into a twin-screw extruder, the aspect ratio of the extrusion screw is in the range of 30:1-40:1, the temperature of the extruder is set at 100-130°C in the T1 zone, 190-205°C in the T2-T5 zone, and 205-210°C in the T6-T12 zone, and the rotation speed is 300-450r / min. After mixing, melting, and homogenizing, the material is extruded and granulated to obtain a light-colored flame-retardant polypropylene composite material that can be used for UV marking.

[0029] The invention also provides application of the polypropylene composite material for ultraviolet laser marking.

[0030] The polypropylene composite material provided by the present invention can also be used to prepare products requiring ultraviolet laser marking.

[0031] Compared with the prior art, the present invention has the following beneficial effects: A light-colored polypropylene composite material provided by the present invention can be used for ultraviolet laser marking and can be widely used in industries and fields such as electronic components, white household appliance shells, and automotive interior and exterior decoration. After ultraviolet laser marking, the material can present a clear laser marking effect. DETAILED DESCRIPTION

[0032] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0033] The raw materials used in the present invention come from: PP resin 1: PP HP500N; homopolypropylene, melt flow rate of 12 g / 10 min at 230°C and 2.16 kg load, CNOOC Shell Petrochemical Co., Ltd.

[0034] PP resin 2: PP T30S (Daqing Refining and Chemical), homopolymer polypropylene, melt flow rate of 3.0 g / 10 min at a temperature of 230 °C and a load of 2.16 kg, Daqing Refining and Chemical.

[0035] PP resin 3: PP EP548R, copolymer polypropylene, melt flow rate is 28g / 10min at a temperature of 230°C and a load of 2.16kg, Suzhou Guihai Plastic Chemical Co., Ltd. Guangzhou Tuma Chemical Co., Ltd.

[0036] PP resin 4: PP EPS30R, copolymer polypropylene, melt flow rate of 1.5 g / 10 min at a temperature of 230°C and a load of 2.16 kg, Shandong Qilu Petrochemical Plant Co., Ltd.

[0037] Flame retardant 1; S-05N, the ingredient is antimony trioxide, which is a kind of antimony flame retardant, Changde Chenzhou Antimony Products Co., Ltd.

[0038] Flame retardant 2: XZ-6800 granules, composed of octabromoether, a type of brominated flame retardant, Shandong Brothers Technology Co., Ltd.

[0039] Flame retardant 3: MCA, composed of melamine cyanurate, Shandong Haiwang Chemical Co., Ltd.

[0040] Flame retardant 4: 2500-G, composed of modified ultrafine magnesium hydroxide, is a type of hydroxide flame retardant, Yingkou Global Powder Engineering Co., Ltd.

[0041] Antioxidant 1: Phosphite antioxidant, YFK-168, Yingkou Fengguang Chemical Co., Ltd.

[0042] Antioxidant 2: Hindered phenol antioxidant, YFK-1010, Yingkou Fengguang Chemical Co., Ltd.

[0043] Light stabilizer: Hindered amine light stabilizer, UV-3808PP5, Cytec Surface Technology (Shanghai) Co., Ltd.

[0044] Composite color powder 1: It is compounded by titanium dioxide and carbon black in a weight ratio of 5000:1, wherein the titanium dioxide is rutile titanium dioxide, TR-33, with a particle size of 0.22um, from Shanghai Yantai Industrial Co., Ltd.; and the carbon black is magicab 1013F, with a primary particle size of 24±2nm, from Shenzhen Dingtai Chemical Co., Ltd.

[0045] Composite color powder 2: It is compounded by titanium dioxide and carbon black in a weight ratio of 10000:1, wherein the titanium dioxide is rutile titanium dioxide, TR-33, with a particle size of 0.22um, from Shanghai Yantai Industrial Co., Ltd.; and the carbon black is magicab 1013F, with a primary particle size of 24±2nm, from Shenzhen Dingtai Chemical Co., Ltd.

[0046] Composite color powder 3: It is compounded by titanium dioxide and carbon black in a weight ratio of 2000:1, wherein the titanium dioxide is rutile titanium dioxide, TR-33, with a particle size of 0.22um, from Shanghai Yantai Industrial Co., Ltd.; and the carbon black is magicab 1013F, with a primary particle size of 24±2nm, from Shenzhen Dingtai Chemical Co., Ltd.

[0047] Test method: UV laser marking performance (△E): S1: Use UV-3X ultraviolet laser marking machine (wavelength of 355nm) to scan and mark a circular mark with a diameter of 25mm on the surface of the standard color plate according to fixed process parameters. The specific operation steps are as follows: first, import the vector image of the pattern to be marked into the EzCad 2.0 software; second, set the appropriate power, scanning speed and other related marking process parameters; finally, preview the marking position and marking pattern, and complete the marking after confirming that they are correct.

[0048] S2: Use Datacolor Sepctro 1050 colorimeter to measure the color data L0, a0, b0 of the color plate before UV laser marking and the color data L1, a1, b1 of the circular area after laser marking, and use the color difference △E before and after marking to characterize the effect of UV laser marking. The specific algorithm is as follows:

[0049] Among them, △L= L1- L0, △a= a1- a0, △b= b1- b0.

[0050] The embodiments and comparative examples of the present invention are prepared by the following steps: The mixed materials are put into a twin-screw extruder, and are extruded and granulated after mixing, melting, and homogenizing to obtain a light-colored flame-retardant polypropylene composite material that can be used for ultraviolet marking.

[0051] The aspect ratio of the twin-screw extruder is 30:1, the extrusion temperature is set to 100-130°C in T1 zone, 190-205°C in T2-T5 zone, 205-210°C in T6-T12 zone, and the rotation speed is 350r / min.

[0052] Table 1 Components of polypropylene composite materials and their test results in Examples 1-9 Serial number Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Example 9 PP resin 1 95 105 100 100 100 100 PP resin 2 100 PP resin 3 100 PP resin 4 100 Flame retardant 1 20 5 5 10 15 20 15 15 15 Antioxidant 1 2.5 0.5 1.5 1.5 1.5 1.5 1.5 1.5 1.5 Antioxidant 2 2.5 0.5 1.5 1.5 1.5 1.5 1.5 1.5 1.5 Light Stabilizer 3 1 3 3 3 3 3 3 3 Composite toner 1 5 0.5 4 4 4 4 4 4 4 UV laser marking performance (△E) 36.31 35.88 38.19 42.48 48.36 46.79 47.81 45.33 42.98 It can be seen from Examples 3-6 that as the amount of flame retardant added increases, the laser marking performance first improves and then decreases.

[0053] It can be seen from Examples 5 and 7-9 that the effect of copolymer PP resin is worse than that of homopolymer PP resin.

[0054] Table 2 Components of polypropylene composite materials and their test results in Examples 10-21 Serial number Example 10 Embodiment 11 Example 12 Embodiment 13 Embodiment 14 Embodiment 15 Example 16 Embodiment 17 Embodiment 18 Embodiment 19 Embodiment 20 Embodiment 21 PP resin 1 100 100 100 100 100 100 100 100 100 100 100 100 Flame retardant 1 15 15 15 15 15 15 15 15 15 Flame retardant 2 15 Flame retardant 3 15 Flame retardant 4 15 Antioxidant 1 0.5 2.5 1.5 1.5 1.5 2 2.5 1.5 1.5 1.5 1.5 1.5 Antioxidant 2 0.5 2.5 1.5 1.5 1.5 1 0.5 1.5 1.5 1.5 1.5 1.5 Light Stabilizer 3 3 3 3 3 3 3 3 3 3 3 3 Composite toner 1 4 4 0.5 2 5 4 4 4 4 4 Composite color powder 2 4 Composite toner 3 4 UV laser marking performance (△E) 39.26 47.22 36.73 37.82 47.88 49.55 42.57 39.75 41.22 43.35 43.99 37.85 It can be seen from Examples 10-11 that adjusting the amount of antioxidant added can affect the laser marking performance.

[0055] It can be seen from Examples 5, 12-14 that the higher the amount of composite color powder added, the better. It is speculated that the reason is that carbon black is a black color powder. Increasing the amount of carbon black will reduce the whiteness of the base color of the material, resulting in a decrease in the color difference before and after UV laser marking, which is manifested as a decrease in UV laser marking performance.

[0056] It can be seen from Examples 5, 15-16 that the weight ratio of the phosphite antioxidant to the hindered phenol antioxidant is preferably (1-3):1.

[0057] It can be seen from Examples 5 and 20-21 that the ratio of titanium dioxide and carbon black in the composite color powder affects the ultraviolet laser marking performance, and the weight ratio of titanium dioxide and carbon black is preferably (4000-6000):1.

[0058] It can be seen from Examples 1-21 that after the polypropylene composite material provided by the present invention is marked by ultraviolet laser, the performance test result ΔE>35, and the polypropylene composite material provided by the present invention has good ultraviolet laser marking performance.

[0059] Table 3 Components of polypropylene composite materials of Comparative Examples 1-4 and their test results Serial number Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 PP resin 1 100 100 100 100 Flame retardant 1 15 15 / 35 Antioxidant 1 1.5 1.5 1.5 1.5 Antioxidant 2 1.5 1.5 1.5 1.5 Light Stabilizer 3 3 3 3 Composite toner 1 0.2 15 4 4 UV laser marking performance (△E) 28.91 29.67 23.36 27.88 It can be seen from Comparative Examples 1-2 that when the amount of the composite color powder added does not reach the required minimum limit or exceeds the maximum limit, the ultraviolet laser marking performance ΔE <30.

[0060] It can be seen from Comparative Examples 3-4 that when no flame retardant is added or an excessive amount of flame retardant is added, the ultraviolet laser marking performance will also be significantly reduced.

Claims

1. A polypropylene composite material, characterized in that: According to weight parts, it includes the following ingredients: Polypropylene resin 95-105 parts; Flame retardant 5-20 parts; 1-5 parts of antioxidant; 1-3 parts of light stabilizer; Composite pigment 0.5-5 parts; The composite pigment is obtained by compounding titanium dioxide and carbon black; the weight ratio of the titanium dioxide and carbon black is (2500-20000):

1.

2. The polypropylene composite material according to claim 1, characterized in that: The melt index of the polypropylene resin is 1-30 g / 10 min. The testing standard is ISO 1133-1-2011, and the testing conditions are a temperature of 230° C. and a load of 2.16 kg.

3. The polypropylene composite material according to claim 1, characterized in that: The polypropylene resin is selected from at least one of homopolymer polypropylene resin and copolymer polypropylene resin, preferably homopolymer polypropylene.

4. The polypropylene composite material according to claim 1, characterized in that: The flame retardant is selected from flame retardants containing metal elements, and preferably the flame retardant is selected from flame retardants containing antimony or titanium elements.

5. The polypropylene composite material according to claim 1, characterized in that: The antioxidant is selected from phosphite antioxidants and hindered phenol antioxidants; the weight ratio of the phosphite antioxidants to the hindered phenol antioxidants is (1-3):1, preferably (1.5-2.5):

1.

6. The polypropylene composite material according to claim 1, characterized in that: The light stabilizer is selected from at least one of a hindered amine light stabilizer, a benzotriazole light stabilizer, a benzophenone light stabilizer or a hindered benzoate light stabilizer.

7. The polypropylene composite material according to claim 1, characterized in that: The titanium dioxide is selected from rutile titanium dioxide.

8. The polypropylene composite material according to claim 1, characterized in that: The weight ratio of the titanium dioxide to carbon black is (4000-6000):

1.

9. The method for preparing the polypropylene composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Weigh each component according to the ratio, put it into the premixer in sequence, and mix them evenly; (2) The mixed materials are fed into a twin-screw extruder, and the mixed materials are extruded and granulated after mixing, melting, and homogenizing to obtain the polypropylene composite material.

10. Use of the polypropylene composite material according to any one of claims 1 to 8, characterized in that: For UV laser marking.

Citation Information

Patent Citations

  • White polypropylene material capable of realizing laser marking, preparation method and application thereof

    CN113845731A

  • Composite material capable of being marked by ultraviolet and near-infrared laser and preparation method of composite material

    CN115521524A

  • High-reflectivity laser marking polypropylene composite material as well as preparation method and application thereof

    CN118580604A